Analisis Pengaruh Belanja Langsung, Belanja Tidak Langsung Dan Penyertaan Modal Pemerintah Daerah Terhadap Pertumbuhan Ekonomi - Sinto, Sinto; Zuhroh, Diana; Sukanti Cahyaningsih, Dyah (GEMA EKONOMI, 2023)
The purpose of this study is to examine the effect of direct spending, indirect spending, and local government equity on economic growth in the province of Central Kalimantan in 2018- 2020. The population in this study were all regencies/cities in Central Kalimantan province, totaling 14 regencies/cities. The sampling technique uses saturated sampling. Data collection techniques using documentation. The data analysis technique used is multiple linear regression analysis. The results of the study show that direct spending and local government equity have a positive effect on economic growth. Meanwhile, indirect spending has no positive effect on economic growth.